Automatic Fault Detection of Transmission Line Using IOT - M. S. Lagad; S. S. Shinde; P. D. Lashkare; Y. R. Bagale; Prof. H. S. Avchat (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The development and advance in technology, many things are changes. The technology laid out to understand its importance like in urban areas, the electrical Line to go Transmission instead of overhead lines, which grab less space and is consider as the effective and efficient way of transmission. But the problem ascends when any fault be occurred in the Transmission Line and it’s also difficult to detect the proper location of the fault during the process of repairing that especial Line and the methods existed till now follows some algorithm in order to scan the location of the fault. The raised system which constitute of current sensors, microcontroller (Node MCU) and Wi-Fi modem which creates a course between the combined hardware and internet so that the real time data can be successively communicated towards server its being successively communicate with towards server and along with this everything becomes smart and interconnected with the help of IoT (internet of things) those are real time data can be retrieved in pc or mobile phones from the server. Hitherward by using useful stage provided by IoT any one can recover information whenever they are necessary. By implementing the proposed system life of the Line will also get by grown because after implementing the system the supply transmission of the power can be closed till the fault gets mend and through this the inessential losses which are developed though the leakage of current can be avoided.